Traumatic Dislocation of the Proximal Tibiofibular Joint: A Systematic Review and 10-year Experience From a Level 1 Trauma Center. (3rd May 2022) - Rajan, Prashant V.; Ramski, David E.; Romeo, Nicholas M.
Abstract : Introduction: Traumatic proximal tibiofibular joint dislocations occur infrequently and are typically the result of high-energy trauma. These injuries can be a marker of limb injury severity because patients often sustain vascular injury and are at high risk of amputation. The purpose of this study was to present a systematic review of traumatic proximal tibiofibular joint dislocations and compare rates of associated injuries with a retrospective series of patients at a level 1 trauma center. The secondary objective was to report rates and clinical predictors of limb amputation. Methods: A systematic review was conducted, identifying three studies meeting eligibility criteria. A retrospective chart review was conducted identifying 17 skeletally mature patients with proximal tibiofibular dislocation treated from January 2010 to February 2021. A chart review extracted patient demographics, fracture patterns, open fracture, preoprative and postoperative peroneal nerve injury, vascular injury, and amputation. Binary logistic regression analysis was used to identify clinical predictors of outcomes. Results: Sixteen of 17 proximal tibiofibular injuries (94.1%) were associated with fracture, most commonly tibial shaft (n = 11, 68.75%). Twelve of 17 fractures (76.5%) were open. Five vascular injuries (29.4%) occurred requiring surgical intervention. Seven (41.2%) preoperative peroneal nerve deficits were noted; six had persistent deficits postoperatively or underwent amputation (average follow-up 31.3 ± 32.6 months). Two patients in the sample without preoperative peroneal nerve deficits were noted to exhibit them after fixation. Eight patients (47%) underwent an amputation, 7 (87.5%) of whom had an open fracture and 4 (50%) of whom had documented vascular injury. Discussion: Traumatic proximal tibiofibular fractures indicate severe injury to the lower extremity with high risk for nerve injury and possible amputation. Patients who present with vascular injury and open fracture in association with proximal tibiofibular joint disruption may be at elevated risk of amputation.